SOLIDARITAS SOSIAL PETANI PADI SAWAH DESA NARUMONDA VII KECAMATAN SIANTAR NARUMONDA KABUPATEN TOBA SAMOSIR SUMATRA UTARA - Daniel Parluhutan Sinambela; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
A study that discusses the social solidarity of rice farmers in Narumonda VII Village, Siantar Narumonda District, Toba Samosir Regency, North Sumatra. The matter discussed in this reseach is how social solidarity is Marsiadapari in the community, whether the culture still exists in the community, whether factors that inhibit or influence social solidarity. The data collection method uses a qualitative research method with a type of descriptive research that aims to broadly describe the social solidarity of rice farmers that is Marsiadapari culture in the community of Narumonda VII Village. The results showed that the Marsiadapari culture was carried out voluntarily by the community and carried out jointly or cooperatively which started from a sense of kinship and mutual need between the village community. This social solidarity was also built because most of the villagers' livelihoods were farming. This makes Marsiadapari culture possible in the village community. The sense of needing one another is also felt by the community. Factors that cause the decline in social solidarity of paddy farmers in Marsiadapari culture are modernization that is growing and of course the advancement of agricultural equipment technology. That gives a big enough influence to the village community to change the mindset of the people of course. This indicates that technological progress and the development of an era that is increasingly innovating and incarnating forms a new civilization in people's lives. These developments also make cultural values in society fade along with existing developments.  Keyword: Social Solidarity, Marsiadapari